Enhancing flame resistance properties and water resistance of rigid polyurethane foam using microencapsulation - Gang Tang; Zedong Gong; Mengru Liu; Yanbei Hou; Kang Tao; Kang Dai; Shihua Zhang (Case Studies in Thermal Engineering)
To enhance the efficacy of flame retardants and their resistance to water in conventional formulations, this work introduces a microencapsulation method to modify the surface of piperazine pyrophosphate (PAPP). This approach improves the compatibility of PAPP with rigid polyurethane foam (RPUF) and incorporates hydrophilic silicone gel (generated SiPAPP), enhancing both flame retardant performance and the synergistic interaction among phosphorus, nitrogen, and silicon elements. Additionally, iron oxide nanoparticles (Nano-Fe2O3) are used to modify the flame retardant surface post-microencapsulation (named as SiPAPP@Fe2O3) to further suppress smoke release. Results indicate that SiPAPP@Fe2O3 facilitates premature decomposition and promotes the development of a stable carbon layers, with the charcoal remains amount of RPUF/SiPAPP@Fe2O3 at 700 °C reaching 32.4 wt%, 1.36 times higher than pure RPUF. XPS analysis of the char residue reveals that silicone gel decomposition generates SiO2, covering on the char surface to form a dense layer. Nano-Fe2O3, acting as a carbon forming agent and synergist agent, together with SiPAPP, promotes the establishment of expanded carbonaceous layer, endowing the RPUF/SiPAPP@Fe2O3 composite with excellent flame retardant properties.